2017
DOI: 10.1111/gwat.12611
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Groundwater Depletion and Drought in the Tigris‐Euphrates Basin Between 2003 and 2015

Abstract: Quantitative estimates of the groundwater depletion and droughts in the Tigris-Euphrates Basin (TEB) can be useful for sustainably managing its water resources. Here, data from the Gravity Recovery and Climate Experiment (GRACE) satellite mission are used to infer the monthly changes in the total water storage of the TEB from January 2003 to December 2015. Additionally, the data of altimetry and output from land surface models are used to remove the contributions from lake water changes and other hydrological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…The overall water storage anomalies in the ETB (Figure 2a) have a steeper trend line after 2007. Chao et al [96] found that the negative trend after the drought (2007-2015) was 3.6 times as large as before the drought (2002)(2003)(2004)(2005)(2006). Similarly, the drought pattern becomes stronger for the KAB, with 2010 as an exception.…”
Section: Changes In Total Water Storagementioning
confidence: 98%
“…The overall water storage anomalies in the ETB (Figure 2a) have a steeper trend line after 2007. Chao et al [96] found that the negative trend after the drought (2007-2015) was 3.6 times as large as before the drought (2002)(2003)(2004)(2005)(2006). Similarly, the drought pattern becomes stronger for the KAB, with 2010 as an exception.…”
Section: Changes In Total Water Storagementioning
confidence: 98%
“…Models developed by different approaches and processing strategies are also provided by other agencies, for example, the Astronomical Institute of the University of Bern (Meyer et al, ), the Delft Institute of Earth Observation and Space Systems (Farahani et al, ), the Groupe de Recherche de Geodesie Spatiale (Bruinsma et al, ), the Huazhong University of Science and Technology (HUST; Zhou, Luo, Zhou et al, ), the Institute of Geodesy and Geophysics, Chinese Academy of Sciences (Wang et al, ), the Institute of Theoretical Geodesy and Satellite Geodesy at the Graz University of Technology (ITSG; Klinger & Mayer‐Gürr, ), the Tongji University (Tongji; Chen et al, ), and the Wuhan University (Guo et al, ). These temporal gravity field models have been widely used in hydrology, oceanology, glaciology, meteorology, and seismology (e.g., Chao et al, ; Humphrey et al, ; Long et al, ; Pan et al, ; Tangdamrongsub et al, ; Tregoning et al, ; Zhou, Luo, Tangdamrongsub, et al, ; Zhou, Luo, Tangdamrongsub, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, groundwater storage changes (GWSC) can be separated from LWSC measures by combining the GRACE data and external information (see and Feng et al [2018] for a review on the use of GRACE for monitoring GWSC). The GRACE mission has proven to be a valuable tool for detecting GWSC at global (Richey et al 2015;Rodell et al 2018) and regional scales (∼160,000 km 2 ) (Rodell et al 2009a(Rodell et al , 2009bVoss et al 2013;Chao et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been plenty of research using GRACE to explore GWSC in various river basins around the world, including the Amazon River Basin (South America) (Frappart et al 2019), Tigris-Euphrates Basin (Middle East) (Chao et al 2018), Congo Basin (Africa) (Ndehedehe et al 2018), Canning Basin (Australia) (Munier et al 2012), Colorado River Basin (USA) (Castle et al 2014), Mississippi River basin (USA) (Rodell et al 2007), and Yellow River Basin (China) (Lin et al 2019), there has seldom been any thorough assessment of GWSC in the Jinsha River Basin (JRB), which is located in the uppermost region of the Yangtze River, China.…”
Section: Introductionmentioning
confidence: 99%